A questionnaire-based Study of Knowledge and Attitude in Healthcare Professionals about Child Sexual Abuse related to POCSO (Protection of Children from Sexual Offences) Act: A Cross-sectional Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The Government of India has passed special law, The Protection of Children from SexualOffences (POCSO) Act, 2012 which provides strong shield for protection of children from heinous crimesof sexual assault, sexual harassment and pornography, there by safe guarding the interest of children at everystage of judicial proceeding.Methodology: A questionnaire based study was carried among 100 healthcare professionals working at thetertiary care Hospital, randomly selected. The questionnaire had 15 Multiple Choice Questions about ChildSexual Abuse related to POCSO Act. Collected data was analysed statistically.Objective: The study is aimed to assess knowledge and attitude about Child Sexual Abuse related to POCSOAct among healthcare professionals.Result: Greater percentage of healthcare professionals have knowledge about major aspects of POCSOAct, as related to its full form (75%), enactment (62%), definition of child (62%), different types of sexualoffence (86%), its mandatory reporting (81%), and trial in child friendly special courts (64%). But in fewareas, knowledge related is scarce as only 40% participants knew punishment scales of POCSO Act and 46%knew failure to report is punishable offence. 84% participants suggest multidisciplinary approach is the needof hour to tackle cases of child sexual abuse.Conclusion: To curb this menace educating health care professionals along with children, spreadingknowledge and awareness at community level with strict law enforcement will play a key role.